Actualización clínico-patológica en la miocardiopatía arritmogénica del ventrículo derecho - Thiene, Gaetano; Pilichou, Kalliopi; Rizzo, Stefania; Valente, Marialuisa; Basso, Cristina (CorSalud, 2017)
Actualización clínico-patológica en la miocardiopatía arritmogénica del ventrículo derecho